2021
DOI: 10.1002/agj2.20755
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic characterization of cotton genotypes susceptible and resistant to reniform nematode in the United States Midsouth

Abstract: Cotton (Gossypium hirsutum L.) genotypes resistant to reniform nematode (RN) (Rotylenchulus reniformis Linford and Oliveira) have been recently developed to reduce yield losses from RN, yet little is known of their agronomic responses under field conditions. This research was conducted to determine if RN population vary cotton growth and development and yield among RN resistant (G. barbadense introgressions; 08SS110-NE06.OP and 08SS100) and susceptible cotton genotypes (Deltapine 16 and PHY 490 W3FE) in enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This would suggest that the variables of growth we studied may not be strong indices of tolerance during early season growth. Thus, the supposition is supported by a related study that showed comparable early season growth and development among susceptible checks and resistant lines (i.e., sowing to 7 weeks after sowing) under RN infested field conditions [51].…”
Section: Discussionmentioning
confidence: 69%
“…This would suggest that the variables of growth we studied may not be strong indices of tolerance during early season growth. Thus, the supposition is supported by a related study that showed comparable early season growth and development among susceptible checks and resistant lines (i.e., sowing to 7 weeks after sowing) under RN infested field conditions [51].…”
Section: Discussionmentioning
confidence: 69%
“…In the recent field study conducted over 2 years (2017 and 2018) of emergence through physiological maturity under infested field conditions. The study revealed overall 29% reduction in main stem length, 11% reduction in the number of nodes on the main stem, 50% reduction in canopy leaf area, and 29% reduction in canopy biomass in the susceptible cultivar PHY 490 W3FE due to reniform nematode infestation compared to resistant cotton line 08SS110-NE06.OP (Figure 3; Singh et al, 2021).…”
Section: Reniform Nematode Effects On Cotton Growth and Developmentmentioning
confidence: 99%
“…However, results of early growth in the greenhouse may not mimic to field Source: http://www.cotton.org/beltwide/proceedings/ outcomes. For instance, cotton plants showed smaller and darker green leaves, and subsequently higher leaf water content and light attenuation through the plant canopy as a tolerance response to reniform nematode under greenhouse conditions (Agudelo et al, 2005;Gausman et al, 1975;Lambe & Horne, 1963;Moore & Lawrence, 2013) but CGR of the cotton canopy in field slow under reniform nematode pressure (Singh et al, 2021). The slow CGR may lead to lower yield (up to 35%) and decrease in yield components such as boll weight (21% lower) and seed weight (23% lower) (Jones et al, 1959;Koenning et al, 2004;Singh et al, 2021).…”
Section: Reniform Nematode Effects On Cotton Growth and Developmentmentioning
confidence: 99%
See 2 more Smart Citations